KAJIAN PROGRAM DANA DESA DALAM MENINGKATKAN PENDAPATAN USAHA TANI PADI SAWAH DI DESA KEMINGKING LUAR KECAMATAN TAMAN RAJO KABUPATEN MUARO JAMBI - Aprizal Aprizal; Ira Wahyuni; Mirawati Yanita (Agros Journal of Agriculture Science, 2024)
The purpose of this study is to describe the picture of the implementation of the 2019-2023 village fund program and to examine the village fund program in increasing the income of rice farming businesses in Kemingking Luar Village. The data used in this study is qualitative data, the method of collection uses: observation, interviews, and documentation. The results of the study indicate that the process of managing village funds includes preparation, budgeting and implementation. The use of village funds by the Kemingking Luar Village government, Taman Rajo District, has followed the technical instructions that have been regulated in the legislation, but in the process it is still not optimal. Factors that influence the management of village funds include supporting factors, namely community participation, facilities and infrastructure. While the inhibiting factors are human resources, technical instructions for managing funds that change every year and communication.